Pathological changes waterproof membranes and their identification - Novotný Marek; Misar Ivan (MATEC Web of Conferences, 2017)
With the development of waterproofing systems based on synthetic membranes, especially mPVC, there is an increase in pathological changes of these membranes. Competing manufacturers and pressure on price of the final product have resulted in usage of unstable or low quality raw materials. After production, these materials keep their specific characteristics, however, their aging is accelerated, i.e. they lose their essential qualitative characteristics very quickly. Very important is the detection of these processes which is possible using chemical analysis (gas chromatography, IR analysis and others) as well as using visual inspection of surface by microscope, including 3D modeling. Very important are weldability tests which identify glass transition temperature of the material. The results can then be used as a basis for correct identification of problems with weldability, nonweldability of synthetic membranes, respectively, as well as for identification of normal or abnormal aging of these materials.